2011
DOI: 10.4103/0971-5916.92640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV among blood donors in a tertiary care centre of north India

Abstract: Background & objectives:India has the second highest HIV population in the world with about 2.5-3.0 million cases. HIV-2 cases among general and blood donor population have also been reported mostly from west and south India. This single centre study was carried out to observe the HIV-1 and HIV-2 prevalence among blood donors from north India.Methods:A total of 2,04,677 people were screened for the presence of HIV infection over the 11 year period (1999 to 2009). Till 2004, a third generation ELISA kit was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 11 publications
6
29
1
3
Order By: Relevance
“…The seropositivity of syphilis was only 0.027% similar to a study by Sinha and Dey 10 in which they found seroprevalence of 0.015%, that was much less as compared to the other studies by Makroo et al, 4 Prabhakar et al, 14 and Singh et al 12 who found a prevalence of 0.23%, 0.22% and 0.5% respectively in their studies. Though treponema pallidum does not survive in the stored blood, but it is considered a lifestyle marker as persons positive for syphilis are also likely to be having other sexually transmitted diseases.…”
Section: Discussionsupporting
confidence: 78%
“…The seropositivity of syphilis was only 0.027% similar to a study by Sinha and Dey 10 in which they found seroprevalence of 0.015%, that was much less as compared to the other studies by Makroo et al, 4 Prabhakar et al, 14 and Singh et al 12 who found a prevalence of 0.23%, 0.22% and 0.5% respectively in their studies. Though treponema pallidum does not survive in the stored blood, but it is considered a lifestyle marker as persons positive for syphilis are also likely to be having other sexually transmitted diseases.…”
Section: Discussionsupporting
confidence: 78%
“…Some researches shows seroprevalence of HIV was 0.44%, 0.54% and 0.56% [22,28,29]. Makroo et al in 2011 reported 0.24% among blood donors [30]. In this study we observed relatively less case (0.04%) of HIV.…”
Section: Tti Status (Hiv and Hbsag) Of Participantscontrasting
confidence: 43%
“…For the third generation ELISA 98·5 and 99·3% for fourth generation assay were repeat reactives. Of the repeat reactives 96% were confirmed positive by the HIV‐1 WB (Makroo et al , ). In a small size ( n = 1075) comparative study, four additional seroreactive samples were observed by the fourth generation assay over the third generation, with only one of the four confirmed by WB (Kaur et al , ).…”
Section: Efforts To Limit Tti Through Blood Screening In Indiamentioning
confidence: 99%